2020
DOI: 10.1016/j.jiac.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Mycobacterium genavense infection mimicking TAFRO syndrome

Abstract: TAFRO syndrome is a rare variant of idiopathic multicentric Castleman's disease, for which disseminated non-tuberculous mycobacteria (NTM) infection must be excluded. However, due to the slow and fastidious growth of the organisms, identification of the pathogen is often challenging. We herein describe a case of disseminated Mycobacterium genavence infection, in which manifestations of the patient were confusingly similar to those of TAFRO syndrome. A 69-year-old Japanese man presented with prolonged fever acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Bone marrow biopsy may also have diagnostic utility, considering the extent of thrombocytopenia observed in our study (the median pre‐treatment platelet: 37 × 10 3 /μl) and that approximately 90% of the cases had either reticulin fibrosis or increased megakaryocytes in the bone marrow specimen. Bone marrow biopsy is feasible without additional platelet transfusion in most cases and may provide useful information to exclude other differential diagnoses such as hidden hematologic malignancy and infectious diseases 41–43 . Given that prior definitions have defined the R in TAFRO as either renal dysfunction or reticulin fibrosis, we recommend defining R as either renal dysfunction or reticulin fibrosis (or other bone marrow features) and looking for one of these features as required of iMCD‐TAFRO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow biopsy may also have diagnostic utility, considering the extent of thrombocytopenia observed in our study (the median pre‐treatment platelet: 37 × 10 3 /μl) and that approximately 90% of the cases had either reticulin fibrosis or increased megakaryocytes in the bone marrow specimen. Bone marrow biopsy is feasible without additional platelet transfusion in most cases and may provide useful information to exclude other differential diagnoses such as hidden hematologic malignancy and infectious diseases 41–43 . Given that prior definitions have defined the R in TAFRO as either renal dysfunction or reticulin fibrosis, we recommend defining R as either renal dysfunction or reticulin fibrosis (or other bone marrow features) and looking for one of these features as required of iMCD‐TAFRO.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow biopsy is feasible without additional platelet transfusion in most cases and may provide useful information to exclude other differential diagnoses such as hidden hematologic malignancy and infectious diseases. [41][42][43] Given that prior definitions have defined the R in TAFRO as either renal dysfunction or reticulin fibrosis, we recommend defining R as either renal dysfunction or reticulin fibrosis (or other bone marrow features) and looking for one of these features as required of iMCD-TAFRO. A previous study reported that adrenomegaly or adrenal ischemia on CT scan could be early signs of TAFRO syndrome, 44 2 and 3, our present definition have been based on rigorous reviews of data from patients of different ethnicities and international discussions to establish a precise iMCD-TAFRO diagnostic definition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we noted no pathological lymph node findings suggestive of TAFRO syndrome similar to the mixed type (mixture of vitreous vascular type and plasma cell type) of multicentric Castleman's disease in this case ( 3 , 19 , 20 ). One case report has described a DNTM case in which manifestations confusingly met the diagnostic criteria of TAFRO syndrome ( 21 ). In that case, the causative organism was M. genavence .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, atypical causes, such as disseminated cytomegalovirus or nontuberculous mycobacterial infections, uncommon types of lymphoma, autoimmune disorders, such as systemic lupus erythematosus, Sjögren's syndrome, or vasculitis, must always be considered. 27,[47][48][49]…”
Section: The Inception Of Tafro Syndromementioning
confidence: 99%